ИСТОРИЯ СТАНОВЛЕНИЯ НАРОДНОГО ПРОСВЕЩЕНИЯ КЫРГЫЗСТАНА (КОНЕЦ XIX НАЧАЛО XX ВЕКА) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
As we know, in recent years there have been many questions about the role of Russia in the development of the education system in Kyrgyzstan. In the early years, after the accession of the peoples of Kyrgyzstan to Russia, new educational institutions appeared. In our opinion, the emergence of these institutions became the first steps in the formation of public education. Later, with the establishment of the Soviet education system in Kyrgyzstan, the opportunity to get an education appeared for the poorest part of the population. In order to increase the literacy rate of the population, the Soviet government organized literacy courses for poor peasants, workers and their families, unified labor schools and teacher training courses. All these steps have become a victory for the peoples of Kyrgyzstan in the field of education.
Keywords: history, fight against illiteracy, education, educational courses